Historical novel in literature - Manchester, Inez Isadore (My University, 1898)
Introduction: It is our purpose to study the historical novel as a product of modern times, simply touching facts relating to the early traces which have appeared in various forms. Unless we have read a truly historic novel, we can scarcely conceive what it is, or what relation it bears to what we ordinarily think of as history – Certainly we cannot appreciate its importance as a means of stimulating and inspiring love and sympathy for the past lives and scenes of which we are a continuation. History properly brings before us the facts of the past; but it is to the historical novel that we turn if we would become a part of those historic facts, for there we have history “touched with ever time.” Life that belongs to some past age or some far away country is portrayed and in that life we seem to enter. Life is given to characters from whom we feel a living inspiration. Indeed the true historic novel would have us respond to the natures and to the surroundings to which it has given this new life. Such is our conception of what the historic novel should mean, and we have many novels which describe and portray leading characters and important circumstances which really existed, bringing before us the customs, conditions, and surroundings of a past century in a manner which enlists our affections and gives us a knowledge unobtainable from the dry facts and statements as history would give them.
Citation: Manchester, Inez Isadore. Historical novel in literature. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Historical Novel; History; Love; Sympathy; Knowledge; Theses; Manuscripts (documents)